Destination leadership: leadership for territorial development. Issue 3 (12th August 2014) - Kozak, Metin; Volgger, Michael; Pechlaner, Harald
Abstract : Purpose: – This paper aims to provide an original body of work that presents and discusses the theory that destination leadership is about proactively shaping the future development of destinations and territories. This is the second part of the special issue of Tourism Review on destination leadership. Design/methodology/approach: – This editorial introduces the papers included and highlights a few general thoughts about the interplay between destination leadership and territorial development. Findings: – This introduction summarizes how the papers in this special issue contribute to two streams of research: first, the papers reflect on the necessity of adapting the specific form and style of destination leadership to the development status of a destination. Second, papers highlight that local stakeholders, local knowledge and the local context, in general, have a high impact on destination leadership. Originality/value: – By summarizing and condensing the various contributions to this special issue, the editorial introduction highlights that destination leadership is about proactively shaping the future of tourist destinations. Furthermore, it argues that this development needs to respect local networks, territorial characteristics, histories and contexts. Therefore, tailoring destination leadership to their own territories seems to be an essential success factor, and in the future, we may want to define Alpine destination leadership, island destination leadership, city destination leadership, etc.